Copolymerized nylon 6 resin with synergistic flame-retardant effect and preparation method thereof
By using phosphorus-containing dibasic acid and low-molecular-weight terminal amino silicone in nylon 6 resin, the problem of taking into account both the flame retardant properties and mechanical properties of nylon 6 resin is solved, and high-efficiency flame retardant and excellent Coexistence of mechanical properties.
Patent Information
- Application Number
- CN202411836516.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art is difficult to maintain the excellence of its other properties while improving the flame retardant properties of nylon 6 resin, especially in terms of mechanical properties and thermal stability.
By selecting phosphorus-containing dibasic acid and low-molecular-weight terminal amino silicone as raw materials, component A is prepared through salt-forming reaction, and copolymerized with caprolactam to obtain a copolymerized nylon 6 resin with a synergistic flame retardant effect.
It achieves the balance between excellent mechanical properties and efficient flame retardant properties of nylon 6 resin, greatly enriching its product types and reducing costs.
Smart Images

Figure CN119409963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copolymerized nylon 6 resin having both excellent mechanical and flame retardant properties, and the synthetic route is simple and the process is environmentally friendly. Background Art
[0002] With the continuous improvement of science and technology, new materials and their products are becoming more and more abundant, among which polymer materials are particularly prominent. There are many types of polymer materials with excellent performance. Nylon materials are one of the polymer materials with better comprehensive performance and wider application fields. However, like most polymer materials, nylon materials are a kind of flammable materials. They cannot extinguish themselves when they encounter fire. They cause countless fires and pose a serious threat to people's lives and property safety. Therefore, it is very necessary to study their flame retardant modification. Nylon 6 is the most common and largest-yield nylon material. It has excellent mechanical properties, electrical insulation, weather resistance and self-lubrication. It is a widely used engineering plastic. At the same time, it is used to manufacture synthetic fibers because of its light weight, wear resistance and resistance to insect damage. However, nylon 6 resin is usually flammable, has a low limiting oxygen index, generates high heat when burning, spreads quickly, and produces a large amount of thick smoke and molten droplets, which limits its application in military clothing, fire clothing, outdoor products, public fabric decorations and other fields with high flame retardant requirements. Therefore, developing flame-retardant nylon 6 resin with excellent comprehensive properties is of great significance to expanding its application scope and increasing its added value.
[0003] The study found that while modifying the flame retardant properties of nylon 6 resin, it will inevitably have a negative impact on its other properties. Therefore, while improving the flame retardant properties, the weakening of other properties should be reduced; on the other hand, to achieve industrial production, cost and environmental issues must also be considered. At present, the methods commonly used to prepare flame retardant nylon 6 resin mainly include two categories: blending and polymerization. The traditional method for preparing flame retardant nylon 6 resin is mainly to add some flame retardants without reactive groups to the nylon matrix. The addition amount of such flame retardants is large, and the dispersion in the resin is uneven, which easily leads to poor physical and mechanical properties of the flame retardant nylon 6 resin obtained; secondly, the addition of certain flame retardants containing reactive functional groups (DOPO type) has poor thermal stability and is easy to decompose during the nylon synthesis process, resulting in a low viscosity of the nylon resin, which cannot meet the strength requirements of engineering plastics. At present, the vast majority of scientific researchers are mainly focused on preparing flame retardant nylon by adding inorganic or organic flame retardants, and there is little research on the synthesis of reactive flame retardants and the preparation of bulk flame retardant nylon resin. Therefore, designing and developing a class of flame-retardant monomers with good thermal stability, high content of flame-retardant elements and strong reactivity has become a key technical issue in the preparation of flame-retardant nylon 6 resin.
[0004] Chinese patent 201110134496.8 relates to a flame-retardant nylon 6 nanocomposite material, which solves the flammability problem of nylon 6 / layered silicate nanocomposite materials. The material is characterized by the use of intumescent flame retardant melamine polyphosphate (MPP) and clay flakes for synergistic flame retardancy, wherein the organic clay is made by reacting protonated ADDT with a clay solution, which can be well peeled off in the resin matrix and enables the composite material to reach UL94-V0 level. Chinese patent CN200810157191.7 discloses a method for preparing synergistic flame retardant nylon 6. First, sodium hydroxide aqueous solution is added to aluminum nitrate and magnesium nitrate aqueous solution at room temperature to react; then dissolved sodium stearate aqueous solution is added to the above reaction system and the reaction is continued; the product is filtered, washed and dried to obtain modified layered magnesium aluminum hydroxide powder; microcapsule red phosphorus, modified layered magnesium aluminum hydroxide powder and nylon 6 pellets are weighed and dried respectively; the above three dried materials are premixed, melt blended and extruded into pellets in a twin-screw extruder, and synergistic flame retardant nylon 6 masterbatch is obtained after drying. The present invention uses ammonium persulfate as an initiator, and the ignition point of the prepared microcapsule red phosphorus exceeds 450°C; when the vertical combustion performance of the nylon 6 composite material reaches V-0 level and the LOI reaches more than 28%, the amount of flame retardant required is small, and the flame retardants used are all cheap halogen-free flame retardants, which can reduce costs. The flame retardant properties of the blended flame retardant nylon composite material obtained by adding flame retardants can be significantly improved, but the mechanical properties decrease significantly. Chinese patent 201510435858.5 relates to a flame retardant nylon 66 copolymer material and its preparation method, which mainly reacts a phosphorus-containing flame retardant with a diamine or a diol to obtain a flame retardant prepolymer, and then reacts the flame retardant prepolymer with a nylon 66 prepolymer to obtain a flame retardant nylon 66 copolymer material. The flame retardant nylon 66 copolymer material prepared by this method has the advantages of less flame retardant addition, excellent mechanical properties, and good flame retardant durability. The vertical burning test can reach UL94V-0 level, and the limiting oxygen index is above 32%. However, the initial decomposition temperature of the phosphorus-containing flame retardant introduced is low, and the resin viscosity of the obtained nylon 66 copolymer material is low and the mechanical strength is poor. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and develop a copolymer nylon 6 resin having both excellent mechanical and flame retardant properties, and the synthetic route is simple and the process is environmentally friendly.
[0006] In order to achieve the purpose of the present invention, the overall inventive concept is: phosphorus-containing dibasic acid and low molecular weight amino-terminated silicone (Mn≤2000) are selected as raw materials, component A is prepared by salt-forming reaction, and then copolymerized with caprolactam to obtain a copolymerized nylon 6 resin with synergistic flame retardant effect.
[0007] The present invention is achieved through the following technical solutions: A copolymerized nylon 6 resin with a synergistic flame retardant effect and a preparation method thereof, wherein the structural characteristics of the copolymerized nylon 6 resin with a synergistic flame retardant effect are as shown in Formula I.
[0008]
[0009] The above n can be any integer between 0 and 23.
[0010] A method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect, characterized in that it mainly comprises the following steps: 1) Select phosphorus-containing dibasic acid and low molecular weight amino-terminated silicone (Mn≤2000) as raw materials, and prepare component A through salt-forming reaction in deionized water; 2) Component A, caprolactam and catalyst are added in a certain ratio, and copolymerization is performed to obtain a copolymer nylon 6 resin with a synergistic flame retardant effect.
[0011] The structural characteristics of the above-mentioned phosphorus-containing dibasic acid are shown in Formula II, and the structural characteristics of the low molecular weight amino-terminated silicone (Mn≤2000) are shown in Formula III, wherein n can be any integer between 0 and 23.
[0012]
[0013] The molar ratio of the phosphorus-containing dibasic acid to the low molecular weight amino-terminated silicone (Mn≤2000) is 1:1-1.01, preferably 1:1-1.005, and the amount of deionized water added is 10-40% of the total mass of the phosphorus-containing dibasic acid and the low molecular weight amino-terminated silicone, preferably 20-30%.
[0014] The feed mass ratio of the above-mentioned component A to caprolactam is 1:5-15, preferably 1:6-10.
[0015] The catalyst is one of phosphoric acid, phosphorous acid and sodium hypophosphite, and the added amount is 0.1-0.5% of the total mass of component A and caprolactam.
[0016] The specific process of the above copolymerization is: after feeding, the air in the high-temperature and high-pressure reactor is replaced with high-purity nitrogen for 3 to 4 times, the temperature is raised to 200 to 210°C, the pressure in the reactor is maintained at 2.0 to 2.5 MPa, and after maintaining the pressure for 2.0 to 3.0 hours, the air is slowly released, and the temperature is continued to be raised to 240 to 250°C, and the air is released to normal pressure to discharge the water in the system, and then the system is gradually vacuumed to reduce the pressure to -0.05 to -0.09 MPa, and the copolymer nylon 6 resin with synergistic flame retardant effect is obtained by releasing the material.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) Select phosphorus-containing dibasic acid with high purity, high flame retardant element content and good thermal stability as one of the comonomers to effectively solve the problem of easy decomposition by heat of some reactive flame retardants; (2) Introducing a low molecular weight amino-terminated silicone (Mn≤2000) structure into the main chain of the nylon molecule can exert the nitrogen-phosphorus-silicon synergistic flame retardant effect while improving the toughness and impact resistance to a certain extent; (3) Aiming at the different requirements of specific downstream applications for the strength, toughness and flame retardancy of copolymer nylon 6 resin, customized, differentiated and functionalized production is achieved, greatly enriching the product variety of copolymer nylon 6 resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the infrared curve of the copolymerized nylon 6 resin with synergistic flame retardant effect prepared in Example 1. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments.
[0020] Example 1 Weigh 2485.2 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (when n=0, the corresponding amino-terminated silicone) and 1600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A1 through salt-forming reaction.
[0021] Weigh 2000.0g of component A1, 20000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain copolymer nylon 6 resin with synergistic flame retardant effect.
[0022] Example 2 Weigh 2485.2 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (when n=0, the corresponding amino-terminated silicone) and 1600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A1 through salt-forming reaction.
[0023] Weigh 2000.0g of component A1, 18000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain the copolymer nylon 6 resin with synergistic flame retardant effect.
[0024] Example 3 Weigh 2485.2 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (when n=0, the corresponding amino-terminated silicone) and 1600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A1 through salt-forming reaction.
[0025] Weigh 2000.0g of component A1, 16000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain copolymer nylon 6 resin with synergistic flame retardant effect.
[0026] Example 4 Weigh 2485.2 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (when n=0, the corresponding amino-terminated silicone) and 1600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A1 through salt-forming reaction.
[0027] Weigh 2000.0g of component A1, 14000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain copolymer nylon 6 resin with synergistic flame retardant effect.
[0028] Example 5 Weigh 2485.2 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (when n=0, the corresponding amino-terminated silicone) and 1600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A1 through salt-forming reaction.
[0029] Weigh 2000.0g of component A1, 12000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain the copolymer nylon 6 resin with synergistic flame retardant effect.
[0030] Example 6 Weigh 6192.7 g of amino-terminated silicone (n=5) and 2400.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A2 through salt-forming reaction.
[0031] Weigh 2000.0g of component A2, 12000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain copolymer nylon 6 resin with synergistic flame retardant effect.
[0032] Example 7 Weigh 9900.2 g of amino-terminated silicone (n=10) and 3100.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A3 through salt-forming reaction.
[0033] Weigh 2000.0g of component A3, 12000.0g of caprolactam and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain copolymer nylon 6 resin with synergistic flame retardant effect.
[0034] Example 8 Weigh 17315.2 g of amino-terminated silicone (n=20) and 4600.0 g of deionized water, add 5343.7 g of phosphorus-containing dibasic acid as shown in formula II under stirring (speed 200 r / min), and prepare component A4 through salt-forming reaction.
[0035] Weigh 2000.0g of component A4, 12000.0g of caprolactam, and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain the copolymer nylon 6 resin with synergistic flame retardant effect.
[0036] Comparative Example 1 Weigh 20000.0kg of caprolactam, 40.0g of sodium hypophosphite and 1000g of deionized water in turn, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, raise the temperature to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to raise the temperature to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain ordinary nylon 6 resin.
[0037] Comparative Example 2 1162.1 g of hexamethylenediamine and 1400.0 g of deionized water were weighed, and 5343.7 g of a phosphorus-containing dibasic acid as shown in the structure of Formula II was added under stirring (rotation speed of 200 r / min), and component A5 was prepared through salt-forming reaction.
[0038] Weigh 2000.0g of component A5, 12000.0g of caprolactam, and 28.0g of sodium hypophosphite, put them into a high-temperature and high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 3 to 4 times, heat up to 205°C, maintain the pressure in the reactor at 2.2MPa, maintain the pressure for 2.5h, slowly release the air, and continue to heat up to 250°C, release the air to normal pressure, discharge the water in the system, and then gradually evacuate the system to reduce the pressure to -0.7MPa, and discharge the material to obtain the copolymer nylon 6 resin with phosphorus-containing flame retardant elements.
[0039] Table 1 Performance data of copolymerized nylon 6 resin with synergistic flame retardant effect prepared in each example and comparative example
[0040] Test standard: Tensile, bending and impact performance test conditions: The tensile, bending and impact specimens were placed in a constant temperature and humidity chamber for 24 hours and tested using a testing machine. The test standards were GB / T 1040.2-2006, GB / T 9341-2008 and GB / T1043.1-2008. Flame retardant performance test: According to ANSI / UL94-2013, the vertical combustion method was used, and the specimen size was 125mm×13mm×1.6mm. Limiting oxygen index test: According to GB / T 2406.2-2009, the specimen size was 80mm×10mm×4mm, the gas flow rate was 40mm / s, the initial oxygen concentration was 25%, and the top surface ignition method was used.
[0041] From the data in Table 1, it can be seen that compared with ordinary nylon 6 resin, the copolymerized nylon 6 resin with synergistic flame retardant effect involved in this patent has obvious improvements in elongation at break, notched impact strength, limiting oxygen index and combustion grade, especially the elongation at break has increased by 3.1~7.9 times, the limiting oxygen index has exceeded 30%, and the combustion grade has reached V-0, showing excellent toughness, impact resistance and flame retardancy. On the other hand, compared with the copolymerized nylon 6 resin containing phosphorus flame retardant elements, the copolymerized nylon 6 resin with synergistic flame retardant effect involved in this patent has better limiting oxygen index and combustion grade than the copolymerized nylon 6 resin containing a single phosphorus flame retardant element due to the synergistic flame retardant effect of nitrogen-phosphorus-silicon, and the toughness is significantly improved.
Claims
1. A copolymerized nylon 6 resin with synergistic flame retardant effect and a preparation method thereof, characterized in that: The structural characteristics of the copolymerized nylon 6 resin with synergistic flame retardant effect are shown in Formula I 。 2. The copolymerized nylon 6 resin with synergistic flame retardant effect according to claim 1, characterized in that: The n can be any integer between 0 and 23.
3. A method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect, characterized in that: The main steps are as follows: 1) Select phosphorus-containing dibasic acid and low molecular weight amino-terminated silicone (Mn≤2000) as raw materials, and prepare component A through salt-forming reaction in deionized water; 2) Component A, caprolactam and catalyst are added in a certain ratio, and copolymerization is performed to obtain a copolymer nylon 6 resin with a synergistic flame retardant effect.
4. The method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect according to claim 3, characterized in that: The structural characteristics of the phosphorus-containing dibasic acid are shown in Formula II, and the structural characteristics of the low molecular weight amino-terminated silicone (Mn≤2000) are shown in Formula III, wherein n can be any integer between 0 and 23. 。 5. The method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect according to claim 3, characterized in that: The molar ratio of the phosphorus-containing dibasic acid to the low molecular weight amino-terminated silicone (Mn≤2000) is 1:1-1.01, preferably 1:1-1.005, and the amount of deionized water added is 10-40% of the total mass of the phosphorus-containing dibasic acid and the low molecular weight amino-terminated silicone, preferably 20-30%.
6. The method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect according to claim 3, characterized in that: The mass ratio of component A to caprolactam is 1:5-15, preferably 1:6-10.
7. The method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect according to claim 3, characterized in that: The catalyst is one of phosphoric acid, phosphorous acid and sodium hypophosphite, and the added amount is 0.1-0.5% of the total mass of component A and caprolactam.
8. The method for preparing a copolymerized nylon 6 resin having a synergistic flame retardant effect according to claim 3, characterized in that: The specific process of the copolymerization is as follows: after feeding, the air in the high-temperature and high-pressure reactor is replaced with high-purity nitrogen for 3 to 4 times, the temperature is raised to 200 to 210°C, the pressure in the reactor is maintained at 2.0 to 2.5 MPa, and after maintaining the pressure for 2.0 to 3.0 hours, the gas is slowly released, and the temperature is continued to be raised to 240 to 250°C, the gas is released to normal pressure, the water in the system is discharged, and then the system is gradually vacuumed to reduce the pressure to -0.05 to -0.09 MPa, and the copolymerized nylon 6 resin with a synergistic flame retardant effect is obtained by releasing the material.
Citation Information
Patent Citations
Method for preparing cooperative flame retardant nylon 6
CN101684196B
Environment-friendly flame-retardant nylon 6 nano composite material and preparation method thereof
CN102241895B
A flame-retardant nylon 66 copolymer material and its preparation method
CN105153415B
Silicon-containing reactive flame retardant nylon resin and preparation method thereof
CN106700067A
Phosphorus-silicon synergistic flame-retardant anti-dripping nylon 6 resin and preparation method thereof
CN112920410A
Cited By
Ternary copolymerized nylon resin as well as preparation method and application thereof
CN120173236A
A ternary copolymer nylon resin, a preparation method and application thereof
CN120173236B
Phosphorus-nitrogen-silicon multi-synergistic halogen-free intrinsic flame-retardant nylon 66 and preparation method thereof
CN121181902A